2021
DOI: 10.7774/cevr.2021.10.2.196
|View full text |Cite
|
Sign up to set email alerts
|

Acute myocarditis associated with anti-COVID-19 vaccination

Abstract: Novel anti-coronavirus disease 2019 mRNA vaccines are rapidly implemented worldwide. Therefore, attention should be given to potentially life-threatening adverse reactions. We report on three young male patients, who developed acute myocarditis 2 days after receiving the second dose of the BNT162b2 vaccine. Primary acute myocarditis was not previously reported in association with vaccines that do not include adjuvants. A high index of suspicion should be maintained in order to diagnose and treat patients who d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 2 publications
0
19
0
Order By: Relevance
“…Subsequently, 10 studies were excluded for the following reasons: inclusion of pediatric cases (n=7) [20] , [21] , [22] , [23] , [24] , [25] , [26] , diagnosis of multisystem inflammatory syndrome (n=1) [27] , analysis of incidence data of a pharmacovigilance database (n=1) [28] and opinion paper (n=1) [29] . Therefore, 39 studies were included; 37 of them [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] provided individual data of 86 participants, forming the pooled cohort. On the other hand, 2 observational studies [67] , [68] reported aggregated data of 43 patients.…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, 10 studies were excluded for the following reasons: inclusion of pediatric cases (n=7) [20] , [21] , [22] , [23] , [24] , [25] , [26] , diagnosis of multisystem inflammatory syndrome (n=1) [27] , analysis of incidence data of a pharmacovigilance database (n=1) [28] and opinion paper (n=1) [29] . Therefore, 39 studies were included; 37 of them [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] provided individual data of 86 participants, forming the pooled cohort. On the other hand, 2 observational studies [67] , [68] reported aggregated data of 43 patients.…”
Section: Resultsmentioning
confidence: 99%
“…After the start of the vaccination campaign in Israel, its Ministry of Health started active surveillance of myocarditis in February 2021 following early reports on the occurrence of myocarditis as a possible adverse side effect [ 6 ]. The first case series in the literature appeared three months later and described three young male patients who had been diagnosed with myocarditis two days after the second dose of the Pfizer-BioNTech vaccine [ 25 ].…”
Section: Myocarditis Pericarditis and Covid-19 Vaccinesmentioning
confidence: 99%
“…The number of hospitalizations regarding nerve palsy also falls out of trend from the last 5-year data further adding fuel to the suspicion. Nevet from Israel has reported three cases of potentially life-threatening acute myocarditis within 2 days of the second dose [ 191 ]. On 9 July 2021, European medicines agency (EMA) enlisted myocarditis and pericarditis as side effects of BNT162b2 [ 192 ].…”
Section: Vaccines Approved For Public Usementioning
confidence: 99%